Neutralizing Antibodies and Their Role in Health and Disease - Shen, Chenguang (Immunology and Immune System Disorders, 2024)
As of July 2023, 209 monoclonal antibody drugs have been approved by the FDA for marketing use, which are widely distributed in the fight against immune diseases, infectious diseases, and neurological and metabolic diseases. In this book, we introduce current monoclonal drug development techniques, delivery and therapeutic application of neutralizing antibodies, development and application of anti-inflammatory factor monoclonal antibodies, research progress and prospect of monoclonal antibodies against human infectious diseases (including SARS-CoV-2, Enterovirus, Herpesvirus, Hepatitis Virus, and Orthopoxvirus), and the research and applications of nanobodies in human infectious diseases. Most of the content of this book is aimed at viral infectious diseases that are widespread and seriously endanger human health. For example, SARS-CoV-2 continues to circulate the world. Enteroviral infections continue to cause morbidity and mortality in susceptible individuals worldwide. Hepatitis viruses continue to constitute a significant global health threat that results in substantial morbidity and mortality; Herpesviruses lead to significant health challenges, notably through conditions like herpes, varicella, zoster, mononucleosis, and various cancers including Kaposi's sarcoma, nasopharyngeal carcinoma, and lymphoma. This book provides valuable insights for designing next-generation monoclonal antibodies.